Faktor Risiko dan Penanganan Kristaluria pada Ternak Sapi - Erni Paremadjangga; Yohanes Simarmata; Tarsisius C Tophianong (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Cattle are one of the contributing livestocks to human needs of animal protein. Crystalluria is urogenital disease characterized by the presence of crsytals in the urine. Crystals can chronically combine and enlarge to form urolith which can reduce productive and reproductive performance of cattle. Urine crystals consist of several types and have different structure based on the constituent substance. Crystalluria formation is also influenced by various factors. This study aimed to determine types and characteristics of crystalluria, risk factors, in vitro factors that can induce crystallization and treatment of crystalluria in cattle. This research used literature study approach. Data were collected based on its relation to the research objectives and then analyzed descriptively. The results showed that silica, struvite, calcium carbonate, and calcium oxalate are the most common types of urolith found in cattle. Crystalluria was differentiated by its morphology, solubility, and color. The incidence of crystalluria was caused by various factors, namely supersaturated urine, diet, urine pH, sex, geographic condition, urease-producing bacterias infection, drugs and crystallization inhibitors. General treatment strategies of crystalluria include provide ad libitum drinking and NaCl salt to increase water intake and urine volume, and specific strategies include dietery restriction of crystallogenic substances and adding acidifier and alkalinizer to diet to modify urine pH. Crystalluria treatment was spesifically based on the type of crystalluria found. Therefore, it was necessary to identify crystalluria to determine the treatment to be given. In vitro factors include storage time, evaporation, storage temperature, urease-producing bacteria contamination can induce crystallization, a falsely positive result.